Measurement of the nuclear charge radii of 8, 9Li: the last step towards the determination of the charge radius of 11Li - Nörtershäuser, Wilfried; Kluge, Heinz-Jürgen (The European physical journal. A, Hadrons and nuclei, 2005)
Nuclear charge radii of 6, 7, 8, 9Li have recently been measured at the GSI on-line mass separator using high-resolution resonance ionization mass spectroscopy. We give a brief description of the experimental method. The results for the charge radii are compared with different theoretical predictions.